Validation of miRNAs as diagnostic and prognostic biomarkers, and possible therapeutic targets in medullary thyroid cancers - Mondin, Alberto; Bertazza, Loris; Barollo, Susi; Pedron, Maria Chiara; Manso, Jacopo; Piva, Ilaria; Basso, Daniela; Merante Boschin, Isabella; Iacobone, Maurizio; Pezzani, Raffaele; Mian, Caterina; Censi, Simona (Frontiers in Endocrinology, 2023)
Introduction: Medullary thyroid cancer (MTC) is a rare type of neuroendocrine tumor that produces a hormone called calcitonin (CT). Thyroidectomy is the preferred treatment for MTC, as chemotherapy has been shown to have limited effectiveness. Targeted therapy approaches are currently being used for patients with advanced, metastatic MTC. Several studies have identified microRNAs, including miR-21, as playing a role in the development of MTC. Programmed cell death 4 (PDCD4) is a tumor suppressor gene that is an important target of miR-21. Our previous research has shown that high levels of miR-21 are associated with low PDCD4 nuclear scores and high CT levels. The aim of this study was to investigate the potential of this pathway as a novel therapeutic target for MTC. Methods: We used a specific process to silence miR-21 in two human MTC cell lines. We studied the effect of this anti-miRNA process alone and in combination with cabozantinib and vandetanib, two drugs used in targeted therapy for MTC. We analyzed the effect of miR-21 silencing on cell viability, PDCD4 and CT expression, phosphorylation pathways, cell migration, cell cycle, and apoptosis. Results: Silencing miR-21 alone resulted in a reduction of cell viability and an increase in PDCD4 levels at both mRNA and protein levels. It also led to a reduction in CT expression at both mRNA and secretion levels. When combined with cabozantinib and vandetanib, miR-21 silencing did not affect cell cycle or migration but was able to enhance apoptosis. Conclusion: Silencing miR-21, although not showing synergistic activity with TKIs (tyrosine kinase inhibitors), represents a potential alternative worth exploring as a therapeutic target for MTC.